National championship competition for 10-year old and under player - Matvienko, O.; Brislin, G.; Hunter, D.; Briner, W.; Nyland, J.; Reeser, J.
Children under 10 years of age do not need national level competition to enjoy the sport. Elite championships are highly stressful events with a great emphasis on winning at all costs. Coaches and parents often are anxious to have their children compete without understanding all of the specifics of young children's physical and psycho-social development. As a result, they promote improper values and set unrealistic expectations for youngsters who are vulnerable at this age, both physically and emotionally. The higher the level of competition, the greater the emphasis on winning. Winning at top levels is assessed by going to tournaments, championships, travel and attainment of external rewards. For some adults, this becomes paramount in their quest for success. They set new objectives of training and competition that may not reflect the interests of children (play for fun, improve skills, be with friends). There are only a few spots available for individuals who are good enough to play at the national level. The selection process may leave the rest of the children with no program to participate in. Budget and facility scheduling may cause elimination of sport programs in which children simply have fun and improve their skills. We believe that the elementary school years should be the time when the basic skills are learned, when children have the opportunity to engage in a broad range of activities. Children of this age are not yet ready for specialization and the pressure of intense competition. It does not mean, however, that young children should not experience competition. Competition is an essential part of training, but should not be the focus. Children will benefit from modified, well-organized, less formal team competitions. They will gain some positive competitive experience that will help them strive for excellence in the future.